Newly discovered reefs in the southern Abrolhos Bank, Brazil: Anthropogenic impacts and urgent conservation needs. Issue 1 (15th January 2017) - Mazzei, E.F.; Bertoncini, A.A.; Pinheiro, H.T.; Machado, L.F.; Vilar, C.C.; Guabiroba, H.C.; Costa, T.J.F.; Bueno, L.S.; Santos, L.N.; Francini-Filho, R.B.; Hostim-Silva, M.; Joyeux, J.-C.
Abstract: The Abrolhos Bank is an area of high ecological, socio-economic importance and harbour the richest and most-extensive coral reefs in the South Atlantic. Here we report the discovery of shallow (12–25 m depth) reef complex with ten large biogenic structures, intermediate between the typical mushroom-shaped pinnacles of the northern Abrolhos Bank (17°–18° S) and the small patch reefs found on the central/southern coast of the Espírito Santo State (19°–20° S). The newly discovered reefs harbour a relatively rich and abundant reef community, with 73 fish and 14 benthic cnidarian species, including endangered and commercially important ones. We discuss on urgent needs of properly mapping and understanding the ecological functioning of this reef system. Information provided here is a baseline for future impact evaluations, particularly considering the recent worst environmental disaster of Brazil from a dam collapse in Doce river that affected the region.